Urban tourism – a revolution of the XXI century (Journal of Geography and Environmental Management, 2016)
The development of urban tourism as one of the types of tourism. Displaying basic terms and concepts of urban tourism and its importance in tourism. On the example of the urban centers of tourism and to promote the products of urban tourism statistics are given and analyzed.
Keywords: city; urban objects; urban tourism; urban tourism products; elements of urban tourism; revolution